A histologic and histomorphometric evaluation of pulpal reactions following rapid palatal expansion - (:unkn) unknown (My University, 2000)
The aim of this study was to investigate the effects of the heavy forces exerted by the rapid palatal expansion (RPE) appliance on the pulpal tissue of anchor premolar teeth and to evaluate these effects by histologic and histomorphometric methods. Materials consisted of 34 sound upper premolars, extractions of which were required as part of orthodontic treatment. Twenty-three teeth were extracted after RPE; the remaining 11 teeth, which had not undergone any orthodontic force, were taken as controls. After extraction, the teeth were prepared for histologic examination under light microscopy. Histomorphometric measurements were performed by using image analysis. The data gained were statistically evaluated by nonparametric tests. The null hypothesis was that there was no difference between pulpal tissues of control and test teeth with respect to different durations of RPE. Our results reveal that the null hypothesis was rejected. Of the parameters evaluated, vessel area and minimum and maximum vessel diameters showed significant differences among the groups. Especially the difference between the control and 3-month groups had marked statistical significance. In conclusion, forces applied by RPE appliances caused an adaptive vascular tissue response, as well as fibrotic changes, in the "affected" upper premolars.
Keywords: Female; Humans; Reproducibility of Results; Adolescent; Male; Time Factors; Bicuspid; Palatal Expansion Technique; Statistics, Nonparametric; Dental Pulp; Tooth Extraction